Carriage and acquisition of extended-spectrum β-Lactamase–producing enterobacterales among neonates admitted to hospital in Kilifi, Kenya - Kagia, N; Kosgei, P; Ooko, M; Wafula, L; Mturi, N; Anampiu, K; Mwarumba, S; Njuguna, P; Seale, A; Berkley, J; Bottomley, C; Scott, J; et al. (Oxford University Press, 2019)
Background Infections caused by extended-spectrum β-lactamase–producing Enterobacterales (ESBL-E) among hospitalized neonates in sub-Saharan Africa pose significant clinical challenges. Data on prevalence and acquisition of ESBL-E carriage among hospitalized neonates in the region are few, and risk factors for transmission are not clearly defined. Methods In a cohort study of consecutive neonatal admissions to Kilifi County Hospital from July 2013 through August 2014, we estimated ESBL-E carriage prevalence on admission using rectal swab cultures and identified risk factors using logistic regression. Using twice-weekly follow-up swabs, we estimated the incidence and identified risk factors for ESBL-E acquisition in hospital using Poisson regression. Results The prevalence of ESBL-E carriage at admission was 10% (59/569). Cesarean delivery, older neonatal age, and smaller household size were significant risk factors. Of the 510 infants admitted without ESBL-E carriage, 238 (55%) acquired carriage during their hospital stay. The incidence of acquisition was 21.4% (95% confidence interval, 19.0%–24.0%) per day. The rate was positively associated with the number of known neonatal ESBL-E carriers and with the total number of neonates on the same ward. Conclusions Carriage of ESBL-E was common among neonates on admission, and in-hospital acquisition was rapid. The dissemination and selection of ESBL-E appears to be driven by hospital exposures, operative delivery, and neonatal ward patient density. Further attention to infection control, patient crowding, and carriage surveillance is warranted.